SANKSI PIDANA SEBAGAI UPAYA PENANGGULANGAN HUMAN TRAFFICKING DI DUNIA MAYA - Agus Wasista Saputra, A. A. Putu; -, Yuwono (Kertha Wicara : Journal Ilmu Hukum; Vol. 04, No. 01, Februari 2015)
Advances in technology are not only accompanied by a positive impact, one form of abusing the crime of human trafficking is a technological advancement in cyberspace. Issues to be discussed as to how the setting of criminal sanctions against the perpetrators of human trafficking in cyberspace in the Indonesian criminal law. Writing this paper is to analyze the arrangement of criminal sanctions in the provisions of the existing legislation for the reduction of human trafficking in cyberspace. The method used in this paper is a normative analysis of the norm because there is a void no detailed regulations governing all aspects of human trafficking both in the virtual world of Electronic Information and Transaction Law and the Law on Combating Trafficking in Persons. Criminal sanctions are one of the most effective means used to combat crime, included human trafficking crime in cyberspace. It can be concluded Electronic Information and Transaction Law and the Law on Combating Trafficking in Persons necessary to be revised so that later along with the rules of criminal sanctions is one of the most effective means can be used to combat the crime of human trafficking in cyberspace.
Keywords: Human Trafficking, Cyber, Criminal Sanctions, Countermeasures